RBMS1 Methylation and mRNA Expression Are Differentially Regulated in Placenta Tissue from Obese Women (P11-131-19). (13th June 2019) - Alvine, Travis; Dhasarathy, Archana; Bundy, Amy; Bhattacharya, Atrayee; Darland, Diane; Hur, Junguk; Perley, Danielle; Johnson, LuAnn; Rusten, Mitchell; Roemmich, James; Larson, Kate
Abstract: Objectives: The maternal diet and obesity adversely affect placental structure/function, inflammation, and alters placental DNA methylation. RNA-binding motif single-stranded interacting protein 1 (RBMS1) regulates DNA replication and gene transcription and is expressed in the placenta. Although specific roles for RBMS1 in the context of obesity have not yet been fully explored, RBMS1 has been linked to type 2 diabetes mellitus risk. No data are available regarding the function of RBMS1 in placental tissue and whether placental expression of RBMS1 is regulated differentially in obesity. Methods: Placental tissue from obese (BMI > 25, n = 15) and non-overweight (BMI < 25, n = 3) women was obtained from The Cooperative Human Tissue Network (CHTN) Western Division at Vanderbilt University Medical Center. Epigenetic changes in placental RBMS1 DNA methylation and histone acetylation were assessed by DNA methylation assays and chromatin immunoprecipitation, respectively. Placental RBMS1 gene expression was measured by RT-PCR and RBMS1 protein localization was assessed by immunohistochemistry. The anti-inflammatory effect of RBMS1 was measured in vitro using human placental fibroblast cells (HS 795.PI). Placental short-chain fatty acids (SCFAs) were measured by gas chromatography-mass spectrometry (GC-MS). Results: RBMS1 mRNA ( P  = 0.0029) and DNA methylation ( P  < 0.05) were increased in placentae from obese mothers. RBMS1 protein expression was localized to placental resident macrophages and fibroblastic cells. In vitro, RBMS1 recombinant protein attenuated LPS-induced IL-6 mRNA expression in HS 795.PI cells ( P  < 0.001), suggesting a possible anti-inflammatory role for RBMS1 in the context of placental inflammation. SCFA analysis demonstrated an increase in placental butyrate ( P  = 0.0327), a known histone deacetylase (HDAC) inhibitor in placenta from obese women. Conclusions: These data suggest a possible anti-inflammatory role for RBMS1 in the context of placental inflammation. Increased placental RBMS1 expression in obese women may serve as an adaptive response to reduce placental inflammation. Funding Sources: USDA Agricultural Research Service Project #3062-51000-052-00D.